2006
DOI: 10.1007/s11427-006-0130-6
|View full text |Cite
|
Sign up to set email alerts
|

A novel approach for estimating growth phases and parameters of bacterial population in batch culture

Abstract: Using mathematical analysis, a new method has been developed for studying the growth kinetics of bacterial populations in batch culture. First, sampling data were smoothed with the spline interpolation method. Second, the instantaneous rates were derived by numerical differential techniques and finally, the derived data were fitted with the Gaussian function to obtain growth parameters. We named this the Spline-Numerical-Gaussian or SNG method. This method yielded more accurate estimates of the growth rates of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 17 publications
0
16
0
Order By: Relevance
“…The CKC method was proposed to describe dynamic changes in bacterial populations exposed to linear concentration increases of a drug. The CKC from BC 99 to BC 1 can be used to calculate the BC 50 and other parameters [17,34,35]. The differential analysis method is based on turbidity to exclude the interference of resting cells in the bacterial population.…”
Section: Discussionmentioning
confidence: 99%
“…The CKC method was proposed to describe dynamic changes in bacterial populations exposed to linear concentration increases of a drug. The CKC from BC 99 to BC 1 can be used to calculate the BC 50 and other parameters [17,34,35]. The differential analysis method is based on turbidity to exclude the interference of resting cells in the bacterial population.…”
Section: Discussionmentioning
confidence: 99%
“…The strain was sampled at one-hour intervals during the first 12 h, and at two-hour intervals thereafter. At least three samples were taken per time point, and the CV (coefficient of variation) was found to be less than 5% [35]. The kinetics curve of batch culture approximates closely to the Boltzmann-Sigmoid curve (R 2 =0.98).…”
Section: Possible Cause Of Aggregated Distributionmentioning
confidence: 79%
“…Though Luria and Delbrück, and Newcombe, noted that colonies from initially resistant cells differ in size and transparency from those appearing at later culture times, neither team offered an explanation of these differences [2,3]. In our previous studies of the relationship between antibacterial drugs and the occurrence and propagation of bacterial resistant mutants, we observed that resistant colonies varied in size and that small colonies invariably appeared at later culture stages [34][35][36][37][38][39][40][41][42][43]. Assuming that one bacterial cell multiplies into 1×10 7 cells after 23-24 divisions at 37°C, a single mutation should occur within 812 h, which can become a visible colony within the next 812 h [25,26].…”
Section: Hypothesize That T1 Phage Is Sufficiently Lethal To E Coli mentioning
confidence: 80%
See 2 more Smart Citations